Chapterhouse: Dune - Herbert, Frank (New York : Ace, 2019)
The survivors from the Old Empire, the Bene Gesserit, are fighting the Honored Matres so they can build a new empire out of the ruins of the old one.
Young Adult
English.
Keywords: Dune (Imaginary place) -- Fiction; Science fiction; Science fiction